Assessment of early complications of Endarterectomy using two techniques (Conventional / Eversion) in patients with Atherosclerotic Carotid Stenosis. - وزاز, يامن; غانم أحمد; حسام كنجو (Latakia University Journal -Medical Sciences Series, 2023)
Objective: the primary goal is to identify the actual incidence of peri-surgical complications associated with Carotid endarterectomy. As for the secondary goal, is to identify any risk factors and technical errors predispose to these complications, Methods: this is a retrospective case-control study, including 56 patients who underwent Carotid endaterectomy in Tishreen University Hospital in Syria during the period between 1-1-2017 and 1-1-2022. Data were collected regarding gender, age, diagnosis, surgical procedure(Conventional _Eversion), and comorbidities such as Diabetes, smoking, previous stroke ,hypertension, Transient Ischemic Attack ,Coronary Atherosclerosis ,contralateral carotid atherosclerotic disease(stenosis or occlusion), and peri-surgical complications and during the next 30 days of follow-up. Results: the sex ratio (M:F) was (3.3:1), and 53.5% of cases were from the age group (61-70) years. Conventional technique consists 80.3%of cases ,smoking patients consist 71.4% of cases , Diabetic patients consist 39.2 % versus non diabetic patients 60.8% . Peri-surgical complication rate was 33.9%, they divided to: Post surgical stroke 17.8%, Hymodinamic unstability( hypotension _ bradycardia)8.9%,Post surgical myocardial infarction 5.3%,Wound hematoma 1.7%, whereas Cranial nerve injury, Wound infection, and cerebral hyperperfusion syndrome were 0% for each. Presenting of contralateral carotid atherosclerotic disease(stenosis or occlusion), hypotension during clamping the carotid artery , the long period of surgery more than two hours , besides presenting of hypertension as a comorbidity are all turned to be risk factors for development of perioperative stroke. Conclusion: the majority of peri-surgical complications of carotid endarterectomy surgery are minor and can be managed conservatively. However, early recognition of these complications, and appropriate management are all of paramount importance for improving the patient's functional outcome.